Mean and lowly things : snakes, science, and survival in the Congo - Jackson, Kate, 1972- (Harvard University Press, 2008)
"In 2005 Kate Jackson ventured into the remote swamp forests of the northern Congo to collect reptiles and amphibians. Her camping equipment was rudimentary, her knowledge of Congolese customs even more so. She knew how to string a net and set a pitfall trap, but she never imagined the physical and cultural difficulties that awaited her."--Jacket